Development of Digital Module of Virtual Reality-Based Measurement Materials Assisted by MOOCs Platform for Class X High School Students - Fahrenda, Veni; Eko Risdianto; Dedy Hamdani (Jurnal Penelitian Pembelajaran Fisika, 2025)
The problems that are often experienced in physics learning in the classroom lie in the limited use of learning media so that students' interest and motivation in learning decrease. Therefore, the purpose of this study is to describe the feasibility of the digital module of Virtual Reality-based measurement materials assisted by the MOOCs platform and describe the students' response to the digital module of Virtual Reality-based measurement materials assisted by the MOOCs platform. The research method is (Research and Development) which uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. To determine the feasibility of learning media and student responses to the media that has been designed so that research instruments are used in the form of expert validation questionnaires and student response questionnaires. The results of the study show that the digital module of Virtual Reality-based measurement materials assisted by the MOOCs Platform is very feasible to be used in the physics learning process in schools, with an average feasibility percentage score of 89.94%. In addition, this study was able to increase students' understanding of concepts with an average percentage score of 85.04%. Based on the results of the field test on the response of students, the digital module of Virtual Reality-based measurement materials assisted by the MOOCs Platform is categorized as very good with an average percentage score of 85.81%. Based on the results of the study, it can be concluded that the digital module of Virtual Reality-based measurement materials assisted by the MOOCs Platform is very feasible to use for physics learning and can increase students' understanding of concepts and get a positive response to students.